From Iqra’ to Motivation: Constructing and Testing a Qur’anic Learning Model Based on Surah Al-‘Alaq (1–5) and Quraish Shihab’s Exegesis - Lukman Banfatin; Nola Fibriyanti Bte Salman (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study examines how Qur’anic learning concepts derived from Surah Al ‘Alaq verses 1–5 influence students’ learning motivation, addressing a gap in previous research that has focused on general religiosity rather than operationalizing a measurable Qur’anic construct based on a specific exegetical source. While earlier studies highlight the role of religious values in shaping motivation, none have quantitatively validated a construct grounded in Quraish Shihab’s interpretation of Surah Al ‘Alaq. A quantitative correlational design was employed using primary data collected through Likert scale questionnaires administered to all 90 students of SMA Integral Hidayatullah Batam. The instrument measured four dimensions of Qur’anic learning concepts (iqra’, ta‘lim, akram, qalam) and four indicators of learning motivation. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings show that students’ understanding of Qur’anic learning concepts is high and positively associated with their learning motivation (r = 0.63, p < 0.001). Regression analysis indicates that this understanding explains 40 percent of the variance in learning motivation, with spiritual value internalization emerging as the strongest contributing dimension. These results demonstrate that Qur’anic learning concepts, when operationalized as a structured construct, have measurable motivational significance. The study suggests that integrating Qur’anic values into instructional design can strengthen intrinsic motivation among Islamic senior high school students. It concludes by recommending further experimental research to test the causal effects of Qur’an-based learning interventions. ABSTRAK Penelitian ini mengkaji bagaimana konsep pembelajaran Qur’ani yang bersumber dari Surah Al ‘Alaq ayat 1–5 memengaruhi motivasi belajar peserta didik, dengan mengisi kesenjangan penelitian sebelumnya yang hanya menyoroti religiositas umum tanpa mengoperasionalkan konstruksi Qur’ani yang terukur berdasarkan sumber tafsir tertentu. Meskipun studi terdahulu menegaskan peran nilai keagamaan dalam membentuk motivasi, belum ada penelitian yang secara kuantitatif memvalidasi konstruksi yang berlandaskan tafsir Quraish Shihab atas Surah Al ‘Alaq. Penelitian ini menggunakan desain kuantitatif korelasional dengan data primer yang dikumpulkan melalui kuesioner skala Likert yang diberikan kepada seluruh 90 siswa SMA Integral Hidayatullah Batam. Instrumen mengukur empat dimensi konsep pembelajaran Qur’ani (iqra’, ta‘lim, akram, qalam) dan empat indikator motivasi belajar. Data dianalisis menggunakan statistik deskriptif, korelasi Pearson, dan regresi linear sederhana. Hasil penelitian menunjukkan bahwa pemahaman siswa terhadap konsep pembelajaran Qur’ani berada pada kategori tinggi dan berhubungan positif dengan motivasi belajar (r = 0.63; p < 0.001). Analisis regresi menunjukkan bahwa pemahaman tersebut menjelaskan 40 persen variasi motivasi belajar, dengan internalisasi nilai spiritual sebagai dimensi yang paling berpengaruh. Temuan ini menunjukkan bahwa konsep pembelajaran Qur’ani, ketika dioperasionalkan sebagai konstruksi terstruktur, memiliki signifikansi motivasional yang terukur. Penelitian ini menyiratkan bahwa integrasi nilai Qur’ani dalam desain pembelajaran dapat memperkuat motivasi intrinsik siswa sekolah menengah Islam. Penelitian ini merekomendasikan studi eksperimental lanjutan untuk menguji efek kausal intervensi pembelajaran berbasis Al Qur’an.